Maqasid al-shariah and Islamic religious satisfation: an empirical study of consumer behaviour of Islamic mortgage in Malaysia - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Abdul Razak, Dzuljastri (2013)
Although previous works have shown that conventional marketing theories were, to a certain extent, able to predict factors influencing halal marketing and Islamic mortgage, these theories fail to capture or accommodate the Islamic perspectives of consumer behaviour. Conventional marketing theories have also been found to be inadequate to expound and explain the Islamic mortgage preference among consumers. In response to this concern, Islamic consumer behaviour theory is proposed to explain the factors that may influence the Islamic mortgage industry. In this study, Maqasid al-Shariah index (MSI) and Islamic Religious Satisfaction Index (IRSI) for Islamic mortgage are developed as the basis of the theory. This study reveals that education and IRSI are instrumental in determining the Islamic home financing preference. IRSI, to a certain extent plays role not only as a mediator but also as a moderator. This study finally contributes in developing an empirical Islamic framework in predicting consumer’s behaviour for in an Islamic mortgage market.